2012
DOI: 10.1063/1.3676619
|View full text |Cite
|
Sign up to set email alerts
|

Structure and magnetism of nanocrystalline and epitaxial (Mn,Zn,Fe)3O4 thin films

Abstract: Nanocrystalline (NC) textured Mn0.5Zn0.6Fe1.9O4 (MZFO) films, grown at room temperature on both isostructural and non-isostructural substrates, show magnetization values significantly suppressed from epitaxial MZFO films. X-ray absorption spectroscopy and x-ray magnetic circular dichroism measurements indicate larger ratios of Fe3+ to Fe2+ ions on the tetrahedral sites in the NC films compared to the epitaxial films. The magnetization loops of the NC films are shifted by 200−400 Oe at low temperatures. No such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The pinning effect of the surface spins of these frozen glassy states at the interface of ferrimagnetic grains could possibly leads to the observed exchange bias effect. Earlier, exchange bias effect was also reported in different single phase ferrite thin films such as Ni-ferrite, MnZn-ferrite thin films [16][17][18]. The observed EB effect in these systems was also speculated due to the pinning effect of the surface spins of a disordered state (glassy states/super paramagnetic (SPM) states) at the interface of the ferrimagnetic grains.…”
mentioning
confidence: 83%
“…The pinning effect of the surface spins of these frozen glassy states at the interface of ferrimagnetic grains could possibly leads to the observed exchange bias effect. Earlier, exchange bias effect was also reported in different single phase ferrite thin films such as Ni-ferrite, MnZn-ferrite thin films [16][17][18]. The observed EB effect in these systems was also speculated due to the pinning effect of the surface spins of a disordered state (glassy states/super paramagnetic (SPM) states) at the interface of the ferrimagnetic grains.…”
mentioning
confidence: 83%
“…The XAS spectra obtained for the Mn L edge and the Fe L edge correspond very well to those published in literature for bulk and thin film ferrites. 4,18,25,27,39,40 In order to obtain more detailed information, XMCD spectra have been measured at both edges. These data are also presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…11 Because of the lattice mismatch and the possible diffusion of titanium into the layer, the magnetic properties of the layer are reported to differ from the bulk properties. 6,9,[15][16][17][18][19] Nevertheless, it was still possible to grow layers directly on SrTiO 3 without such buffer layers although the layers exhibited lattice parameters pointing to a large strain, which might be the reason of the variations in the films. Additionally, ferrites grown without buffer layers have shown magnetic properties, which makes them interesting candidates for various applications.…”
Section: -11mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the well-studied antiferromagnet-ferromagnet interface, exchange bias has been observed in spin glasses, systems containing only hard and soft ferri-or ferro-magnets, and sometimes even in ferrimagnets that are biased by their own amorphous microstructural phases [12][13][14][15]. In particular, ferrimagnetic spinel-structure oxides have been studied as model systems for this type of exchange bias [16,17]. Previously, Venzke et al demonstrated that a nanocrystalline thin film of NiFe 2 O 4 exhibited exchange bias even without an external biasing layer.…”
mentioning
confidence: 99%